Ca(2+)-induced self-assembly in designed peptides with optimally spaced gamma-carboxyglutamic acid residues - Dai, Qiuyun (2010)
We have previously elucidated a new paradigm for the metal ion-induced helix-helix assembly in the natural γ-carboxyglutamic acid (Gla)-containing class of conantokin (con) peptides, typified by con-G and a variant of con-T, con-T[K7Gla]. independent of the hydrophobic effect. In these “metallo-zipper” structures, Gla residues spaced at i, i + 4, i + 7, i + 11 intervals, which is similar to the arrangement of a and d residues in typical heptads of coiled-coils, coordinate with Ca(2+) and form specific antiparallel helical dimers. In order to evaluate the common role of Gla residues in peptide self-assembly, we extend herein the same Gla arrangement to designed peptides: NH(2)-(γLSγEAK)(3)-CONH(2) (peptide 1) and NH(2)–γLSγEAKγLSγQANγLSγKAE–CONH(2) (peptide 2). Peptide 1 and peptide 2 exhibit no helicity alone, but undergo structural transitions to helical conformations in the presence of a variety of divalent cations. Sedimentation equilibrium ultracenrifugation analyses showed that peptide 1 and peptide 2 form helical dimers in the presence of Ca(2+), but not Mg(2+), Folding and thiol-disulfide rearrangement assays with Cys-containing peptide variants indicated that the helical dimers are mixtures of antiparallel and parallel dimers, which is different from the strict antiparallel strand orientations of con-G and con-T[K7γGla] dimers. These findings suggest that the Gla arrangement, i, i + 4, i + 7, i + 11, i + 14, plays a key role in helix formation, without a strict adherence to strand orientation of the helical dimer.